Pituitary metastasis as the first manifestation of lung carcinoma - Amaral, Sara (2022)
Pituitary metastases are rare. Clinical presentation could range from asymptomatic to panhypopituitarism or local symptoms. We present a case report of a 43-year-old male patient with a new onset headache, visual disturbances, and panhypopituitarism. The investigation led to the diagnosis of pituitary metastasis as the first manifestation of underlying lung cancer.